The Influence of OHS (Occupational Health and Safety) and Motivation on Employee Performance at CV. Umega Abadi Sanjaya - Sabbiel Hanurama Vladenska; Rahadiansyah Permana (PT Mattawang Mediatama Solution, 2023)
Improving the performance of employees in the company is marked by the work results and work achievements achieved. Improving the performance of employees in the company will be achieved if the company pays attention to Occupational Health and Safety (OHS), provides motivation to employees in an effort to develop all abilities and skills in the form of education, training, providing incentives, using complete and modern workshop facilities, to creating a conducive work environment. The above will be able to spur the enthusiasm of the employees so that the achievement of good performance in accordance with the company's expectations can be realized. This study entitled The Influence of Occupational Health and Safety and Motivation on Employee Performance. The purpose of this study was to determine the effect of Occupational Health and Safety (OHS) programs on employee performance, the effect of motivation on improving employee performance, and a company effort to further improve employee performance for the advancement of CV. Umega Abadi Sanjaya. The research method used is descriptive and verification methods. The population of this research is employees of CV. Umega Abadi Sanjaya. The sampling technique using the formula N = n obtained as many as 30 people, the method of analysis of this study uses multiple regression and hypotheses. The results of this study indicate employee performance is influenced by Occupational Health and Safety and motivation simultaneously. This can be seen by the value t count of 3,306 >t table of 1.70329 with a significance value of 0.003 <0.05. While motivation also has a positive and significant effect on the performance of CV employees. Immortal UmegaSanjaya is proven true. It can be by value count of 2.322 >t table of 1.70329 with a significance value of 0.027 <0.05. Thus it can be concluded that simultaneously or together the variables of Occupational Health and Safety and motivation variables have a positive and significant effect on employee performance. From the results of the analysis, the coefficient of determination (R2) is 0.531. That is, the two variables of occupational health safety and motivation contribute 53.1% together, while the remaining 46.9% is in other studies